Pengelolaan Air Limbah Hotel Dan Pemanfaatannya Dalam Pembangunan Pariwisata Berkelanjutan - Septi Ayu Andini; I Nyoman Sukma Arida (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2019)
Nusa Dua tourism area shaded by PT. Indonesia Tourism Development Corporation (ITDC) has been known as a center of international tourism area that reflects the characteristics of international standards for all facilities built. ITDC has an integrated wastewater treatment system called